Physiklehrbücher im Fokus der fachdidaktischen Forschung - ein internationaler Literatur-Review - Jonas-Ahrend, Gabriela; Kapanadze, Marika; Mazzolini, Alexander; Joubran, Fadeel

Ergebnisse einer Reviewstudie zur Evaluation von Physiklehrbüchern - Jonas-Ahrend, Gabriela; Kapanadze, Marika; Mazzolini, Alexander; Joubran, Fadeel

Academic self-concepts of pre-service technology teachers for vocational education in Germany according to the TPACK- Model - Vernholz, Mats (Living and Leading in the Next Era: Connecting Teaching, Research, Citizenship and Equity)

Work in Progress: Development of a Virtual and Interactive Microgrids Learning Environment for Microgrids Sustainability – The case of East Africa - Bogere, Paul; Bode, Henrik; Temmen, Katrin (Learning in the Age of Digital and Green Transition. ICL 2022. Lecture Notes in Networks and Systems)
Partial coverage of the traditional grid is one of the factors that con-tribute to the low electrical energy access levels in developing countries. This often results in long distances between the grid and unconnected communities. Microgrids, due to their distributed energy resources, have the potential to increase energy access levels. However, there is limited access to microgrids-related knowledge. The knowledge is essential for the effective and efficient use of energy, operation, and hence sustainability of microgrids. To contribute to the sustainability of microgrids, a Virtual and Interactive Microgrids Learning Environment (VIMLE) for microgrids knowledge transfer is developed. VIMLE development is guided by design-based research. With knowledge transfer and skills acquisition through the use of VIMLE, local capacity for designing, installing, operating and maintenance of microgrids is built. Skilled local capacity will contribute to microgrids sustainability. Hence, improve electrical energy access levels and contribute to the achievement of SDG 7.
Keywords: Knowledge Transfer; Microgrids; Sustainability

Knowledge Transfer Concepts for Microgrids Sustainability - The Case of East Africa - Bogere, Paul; Temmen, Katrin; Bode, Henrik (2023 IEEE Global Engineering Education Conference (EDUCON))

Skill Sets for Microgrids Sustainability - The Case of East Africa - Bogere, Paul; Bode, Henrik; Temmen, Katrin (2023 IEEE AFRICON)

Teacher Educators' Experiences and Expressions of Emotion During the Pandemic: International Perspectives - Newberry, Melissa; Rizvi, Meher; van der Want, Anna; Jonas-Ahrend, Gabriela; Kaldi, Stavroula; Kihara, Toshiyuki; Franco, Juan Vicente Ortiz; Ratnam, Tara (Advances in Research on Teaching)

Teaching Technologies: Continuous Interplay Between Educational and Industrial Advances - Jonas-Ahrend, Gabriela; Vernholz, Mats; Temmen, Katrin (Teacher Education in the Wake of Covid-19)
The field of teaching technologies is in constant interplay between educational and industrial advances. Since the beginning of the twenty-first century, digitalization and automatization have become increasingly important. In industrial and social life, we see similar fast-moving developments. These factors challenge education, specifically vocational education, greatly, and raise two very different, yet very much connected questions: how to prepare students for their vocational lives and how to prepare teachers to communicate the necessary competencies to their students? This chapter provides an overview of advances, challenges, and possible solutions, focusing on the three key fields of vocational education in Germany: Industry 4.0, Education 4.0, and innovative teacher education. Most importantly, however, the text examines the continuous interplay between and among these fields. The beginning of the chapter is dedicated to vocational teacher education, in accordance with industrial and educational advances. Specifying this, characteristics of Industry 4.0, as well as students' and teachers' perceptions of Industry 4.0, are discussed. This is followed by an introduction to the concept of so-called learning factories as a possible way of integrating aspects of Industry 4.0 in German vocational schools. The end of the chapter is dedicated to the required changes in educational settings today and in the future. Though Industry 4.0, Education 4.0, and innovative teacher education are each widely discussed in the current literature, the interplay of all three fields reveals a research gap. This chapter tries to close this gap and provide an important contribution to the research field.

Gewerblich-technische Lehrkräftebildung in Deutschland – Analyse der Einflüsse auf das akademische Selbstkonzept von Lehramtsstudierenden technischer (beruflicher) Fachrichtungen - Vernholz, Mats; Temmen, Katrin

Evaluation of Physics Textbooks - Kapanadze, Marika; Jonas-Ahrend, Gabriela; Mazzolini, Alexander; Joubran, Fadeel (The International Handbook of Physics Education Research: Special Topics)
Physics textbooks are generally viewed as important tools that provide well-presented and reliable information that supports and enhances students' understanding of critical concepts. The main goal of this chapter is to find out what attention has been given to textbook evaluation in physics education research literature. Studies about physics textbooks from different countries and different eras are discussed and analyzed, and a broad overview about aspects that influence the efficacy of physics textbooks are presented. Research papers that discuss the importance and influence of digital textbooks (and similar technological resources) are also analyzed.

Teacher Educators' Experiences and Expressions of Emotion During the Pandemic: International Perspectives - Newberry, Melissa; Rizvi, Meher; van der Want, Anna; Jonas-Ahrend, Gabriela; Kaldi, Stavroula; Kihara, Toshiyuki; Franco, Juan Vicente Ortiz; Ratnam, Tara (Advances in Research on Teaching)

Entwicklung eines neuen Konzeptes zur Vermittlung von Lerntechniken und Selbstlernkompetenzen für Studierende des Maschinenbaus an der Universität Paderborn - Bentrup, Leon Alexander; Gräßer, Melanie; Temmen, Katrin; Schmid, Hans-Joachim (die hochschullehre)

Work-in-Progress: The Potential of Interactive Scripts – Supporting Conceptual Understanding and Collaborative Problem-Solving Skills - Temmen, Katrin; Kersten, Peter; Schäfer, Dominik (Mobility for Smart Cities and Regional Development - Challenges for Higher Education)

Wie bewährt sich das duale berufliche Ausbildungssystem der industriellen Metall und Elektroausbildung unter Pandemiebedingungen? Lehrkräfte und Auszubildende reflektieren - Jonas-Ahrend, Gabriela; Vernholz, Mats; Temmen, Katrin (Berufsausbildung zwischen Hygienemaßnahmen und Lockdown(s): Folgen für die schulische und außerschulische Berufsausbildung in Schule, im Betrieb und bei Bildungsträgern)

Von der Präsenz-Blockveranstaltung zum Blended Learning-Konzept - Graefe, Grit; Temmen, Katrin (Hochschullehre erforschen)

Effects on primary and secondary school students’ academic out-of-school learning experiences in Science Technology Engineering Mathematics (STEM) education. Single Paper. ECER (European Conference on Educational Research) 2022 PLUS. “Education in a Changing World: The impact of global realities on the prospects and experiences of educational research” - Schulze, Jan Roland; Crummenerl, Lena Luise; Sicking, Annika; Temmen, Katrin; Blumberg, Eva

Industrie 4.0 in der beruflichen Bildung – Automatisierter Maschinenbaulernbetrieb Paderborn - Vernholz, Mats

Digitale Begleitseminare im Praxissemester der gewerblich-technischen Fachrichtungen - Jonas-Ahrend, Gabriela; Vernholz, Mats; Temmen, Katrin
In diesem Beitrag werden die Elemente „Begleitseminar“ und „Begleitforschungsseminar“ des Praxissemesters für Lehramtsstudierende der beruflichen Fachrichtungen Maschinenbautechnik und Elektrotechnik an der Universität Paderborn im Hinblick auf die Veränderungen durch die Covid-19-Pandemie erläutert.

Projekt Art-D Grids: Nachhaltige und stabile Microgrids in Afrika - eine Plattform für Forschung und Lehre für die Entwicklung - Krauter, Stefan; Böcker, Joachim; Freitag, Christine; Hehenkamp, Burkhard; Hilleringmann, Ulrich; Temmen, Katrin; Klaus, Tobias; Rohrer, Nicolaus; Lehmann, Sven (Tagungsband des 36. PV-Symposiums, 18.-26 Mai 2021)
Keywords: Art-D; Afrika; Resilienz; Resilience; Grid stability; robustness; microgrids

Rekrutierungspotenzial für das Lehramt gewerblich-technischer Fachrichtungen aus dem Beruflichen Gymnasium mit Schwerpunkt Technik? - Graefe, Grit; Temmen, Katrin (Bildung und Beruf, Zeitschrift des Bundesverbandes der Lehrkräfte für Berufsbildung e.V.)